Exposição aguda ao cádmio reduz a atividade da enzima conversora de angiotensina I e aumenta a concentração tecidual do metal - Broseghini Filho, Gilson Brás (2015)
Cadmium exposure causes health problems that may result from increased oxidative stress and from changes in enzyme metaloproteases activities as angiotensina converting enzyme (ACE). In fact, cadmium produces inhibition of serum ACE, but is not known how cadmium acts on tissue ACE activity and whether following acute exposure tissue cadmium content is increased. In order to elucidate these issues, a cadmium bolus was injected intravenously in Wistar rats and the cadmium content and the ACE activity were measure in the serum, lungs, aorta and kidneys. Moreover, in order to clarify if the cadmium affects directly tissue ACE activity, acute metal exposure in vitro was performed. Our results demonstrated that 120 minutes following cadmium administration, blood and organ cadmium content were both increased. Serum and lung ACE activity were reduced following acute cadmium exposure, but aortic and kidney ACE activity were not affected. The inhibitory effects induced by cadmium on ACE activity were also observed in the serum, as well as the lungs and the aorta, but not in the kidneys following in vitro exposure. Moreover, the inhibitory effects induced by cadmium on ACE activity were partially restored in vitro by zinc supplementation, suggesting a possible interaction or competition between cadmium and zinc by at the active site of ACE. Summarizing, our results suggest that acute cadmium exposure promotes an increase in the tissue metal content that was accompanied by direct inhibition of serum, aorta and lung ACE activity, an effect that is cadmium concentrationdependent and is partially reversed by zinc.